Analisis Efektifitas Penggunaan E-Modul Sebagai Bahan Ajar Mata Kuliah Evaluasi Pembelajaran - Iskandar Iskandar; Nina Ikhwati Wahidah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Learning Evaluation is a compulsory subject in the Faculty of Education. Students must pass for the course. Therefore, it is necessary to develop learning materials that are innovative and easily accessible anywhere. One of the learning materials that can be used anywhere and anytime is an electronic module or can be called (e-module). The purpose of this research is to see an analysis of the effectiveness of using e-modules as learning materials for learning evaluation courses. The research method used is quasi-experimental, this research is classified as pre-experimental research. One group pretest and posttest to see the effectiveness of increasing student learning outcomes before and after using the learning evaluation e-module. The sample in this study were 56 students obtained by random sampling. The results of this study are the use of learning evaluation e-modules which can be seen from the results of the t-paired test, based on the results of the paired t-test significance 2-tailed is 0.000 <0.05, it can be concluded that there is a difference between the results of the initial test and the final test using the learning evaluation e-module to improve student learning outcomes. Furthermore, for the t-count value of 16.177, then for the t-table with df 55 it is 3.94. The t-count value is 13.177 > 3.94 so it can be concluded that there is a significant difference in the results of the pre-test and post-test after being treated with the use of the learning evaluation e-module to improve student learning outcomes.